Association of Galectin-3, Lipid Profile, Creatine Kinase-MB in Heart Failure Patients with Preserved Ejection Fraction and Reduced Ejection Fraction - Qais Falih Hassan; Maher Abbood Mukheef; Hameed Hussein Tawafan (Karbala Journal of Medicine, 2025)
Background: Heart failure (HF) is a progressive condition frequently associated with hypertension, type 2 diabetes mellitus, and obesity, contributing to myocardial stress and remodeling. The interaction among galectin-3, lipid profile, and creatine kinase-MB (CK-MB) plays a pivotal role in assessing both preserved and reduced ejection fraction (EF). These biomarkers are essential for diagnosis, prognosis, and risk stratification in HF. Measurement of galectin-3, lipid profile, and CK-MB levels may enhance the predictive capacity for HF. Methods: A case-control study included a total of 90 individuals aged 45–70 years who were involved: 60 HF patients (30 with preserved ejection fraction and 30 with reduced ejection fraction) and 30 age- and sex-matched healthy controls. Five milliliters of venous blood were collected from each participant to measure galectin-3, lipid profile, and CK-MB. Statistical analyses were performed using SPSS for Windows 10 (IBM SPSS 26.0, Chicago, IL, USA). Results: Galectin-3 levels were significantly higher in HF patients (p < 0.001): preserved EF (2201 ± 261), reduced EF (1329 ± 183), and controls (574 ± 120). The lipid profile showed significant increases (p < 0.01) in total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), and very low-density lipoprotein cholesterol (VLDL-C), with a notable decrease in high-density lipoprotein cholesterol (HDL-C) (p < 0.01). CK-MB levels showed no significant difference (p = 0.724). These findings suggest galectin-3 may be a more reliable HF biomarker than CK-MB. Conclusions: Galectin-3 is markedly elevated in HF. Dyslipidemia contributes to HF progression. CK-MB lacks diagnostic significance in this context.